2018
DOI: 10.7202/1042923ar
|View full text |Cite
|
Sign up to set email alerts
|

Continuous monitoring of cyanobacterial blooms: benefits and conditions for using fluorescence probes

Abstract: In situ fluorescence probes have attracted growing interest for the on-line monitoring of cyanobacteria in drinking water treatment plants. The probes rely on the fluorescence of pigments such as phycocyanin and chlorophyll-a to detect respectively cyanobacteria and green algae. They offer direct and simultaneous multiparameter measurements and opportunity for online monitoring which can enable water operators to improve cyanobacteria management during the drinking water process. However, fluorescence probes c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…In lake water, a background fluorescence reading of 0.2 RFU is also noted for DOC of 6.31 mg/L (Figure 1b,d). These findings are in agreement with a prior study reporting a 0.8 RFU phycocyanin signal increase in a commercial humic acid solution (DOC of 10 mg/L) [51].…”
Section: Impact Of Nom On Phycocyanin Probe Performancesupporting
confidence: 93%
See 1 more Smart Citation
“…In lake water, a background fluorescence reading of 0.2 RFU is also noted for DOC of 6.31 mg/L (Figure 1b,d). These findings are in agreement with a prior study reporting a 0.8 RFU phycocyanin signal increase in a commercial humic acid solution (DOC of 10 mg/L) [51].…”
Section: Impact Of Nom On Phycocyanin Probe Performancesupporting
confidence: 93%
“…For instance, Turner Cyanofluor corrects the interference from dissolved organic carbon (DOC) using a filtrate blank [49]. In the actual experimental situation, recent research has shown a significant impact of NOM on phycocyanin probe response to cyanobacterial cells, but the different water matrix, types of NOM investigated, type and presence of cyanobacterial cells, and type of probe investigated were limited [37,50,51]. Furthermore, DOC concentration in the study of Bertone et al [50] was measured by a YSI EXO2 fDOM sensor, which is not as reliable as direct DOC measurements and does not provide information on the adsorption spectra of the NOM.…”
Section: Introductionmentioning
confidence: 99%